Catch me if you can: viral nucleic acids to host sensors - Jung, Yohan; Grainger, Harmony; Yang, Shizhuo; Mondal, Sohaumn; Lukong, Kiven Erique; Conn, Kristen; Wu, Yuliang (Frontiers in Immunology, 2025)
The 2002 movie Catch Me If You Can is a cat-and-mouse story in which Frank Abagnale Jr. successfully conned his way into several high-profile jobs while evading capture by FBI agent Carl Hanratty. Similarly, after entering host cells, viruses interact with or hijack host cellular machinery to replicate their genetical materials and assemble themselves for the next round of infection. Analogous to an FBI agent, host cells have numerous molecular “detectives” that recognize viral nucleic acids (NAs). These include RIG-I, MDA5, LGP2, TLR3, TLR7, TLR8, DHX36, DICER1, PKR, OAS1, ZAP, and NLRP1/6 for viral RNA, as well as cGAS, TLR9, AIM2, IFI16, IFIX, Ku70, MRE11, RNA polymerase III, hnRNPA2B1, LRRFIP1, DAI, DHX9 and DDX41 for viral DNA. However, much like the brilliant Frank Abagnale Jr., viruses have developed various strategies to evade host cellular surveillance—for example, by sequestering or modifying viral NAs and inhibiting or degrading host sensors. In this review, we will summarize the host sensors identified so far, discuss the latest understandings of the various strategies employed by viruses, and highlight the challenges associated with drug development to target virus or host factors. Considering recent global health challenges such as the COVID-19 pandemic and undergoing measles outbreak, understanding virus-host interactions at the molecular and cellular levels remains essential for the development of novel therapeutic strategies.